If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -1y = 0 Solving 20x + -1y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 20x + -1y + y = 0 + y Combine like terms: -1y + y = 0 20x + 0 = 0 + y 20x = 0 + y Remove the zero: 20x = y Divide each side by '20'. x = 0.05y Simplifying x = 0.05y
| 3x+6=8x+3 | | 14=3w-w | | m/42=60/84 | | 27x^2-3x-10=0 | | B+4+4+b= | | 5.49-4.12x-1.4x=32.538 | | y/6-3=11 | | 1.50c+6=4.20 | | 12(5y+4)= | | 11x^11=54x^9 | | 2*600=x*1000 | | 0=1.5t^2-6t+3 | | 6x-2x+7=-6+13 | | X-10y=-86 | | 3/213 | | x^2-17x^2=-72 | | -3/5(5) | | 27+x*x=2x*x | | 3*500=x*1000 | | 5z+3=2z | | x^3-5x+6=y^2 | | 4+h-8-h=0 | | 2/7=35/x | | (3a-2)(4a+5)= | | 2.6+z=-9 | | 20-2r=s | | asP=2(l+w) | | -7f=5 | | -23x-4=7/18 | | 10x-14=41-x | | -7f=51 | | 2x^3+10x+10=0 |